The legal effects of EU agreements - Mendez, Mario (Oxford studies in European law, 2012)
A comprehensive analysis of the legal effects of EU agreements explored in both comparative perspective and in terms of the ramifications for the legal orders of the member states. The book provides a thorough analysis of the case-law in this increasingly important area of EU law, valuable to academics and practitioners alike.
Keywords: Administrative law : European Union countries